Precision medicine for early breast cancer radiotherapy: Opening up new horizons?. (May 2017) - Bernier, Jacques
Abstract: So far most efforts put forth to test the value of predictive and prognostic tools in the field of breast radiotherapy remained globally disappointing, or at least below the convincing levels reached for systemic therapy. Nevertheless the addition of predictive tools to the clinical armament tends to prevail over the use of the sole prognostic factors, also in radiotherapy. A number of predictive assays, clinically validated or not, have recently elicited significant associations between molecular profiles and tumor biological aggressiveness and/or radiosensitivity levels. Will it take a long time for these radiation-specific assays to provide added value to the – already crowded – constellation of predictive tools in the breast cancer? On the one hand, optimizing radiotherapy through the integration of precision medicine into the breast cancer management still remains a challenging issue. On the other hand, recent advances in predictive assays aimed at distinguishing patients with a more radioresistant tumor that necessitates radiation dose escalation or a switch to therapeutic approaches other than radiotherapy, plea in favor of an increasing role, in a near future, for radiation-specific molecular signatures. Streamlining predictive assays platforms via concerted actions should imperatively be given high priority, also in terms of health economics.